Respuesta hemodinámica modificada por Ondansetron en pacientes sometidas a cesárea electiva con bloqueo espinal - Cedillo Muñoz, Anyella (2022)
Sympathectomy produced by spinal anesthesia induces hemodynamic changes; The height of the blockade determines the extent of sympathetic blockade, which in turn determines the magnitude of change in cardiovascular parameters; Hypotension and bradycardia are the most common side effects of sympathetic denervation(4). The BENZOLD JARISCH (RBJ) reflex is part of the vagal reflexes that make up the autonomic nervous system. Its name configures a triad of cardiopulmonary responses to certain stimuli of a mechanical nature (hypercontraction, pressure, distension and changes in volume); in mechanoreceptors, located mainly in the posteroinferior region of the left ventricle. It can also be triggered by endogenous chemical stimuli produced in situations of physiological stress and by pharmacological agents such as selective serotonin receptor agonists; 5 HT-3 receptors are present in the area postrema of central and peripheral nerve terminals, in the trigger zone of chemoreceptors(6); Ondansetron is a selective antagonist of 5 Hydroxytryptamine (5 HT-3) receptors.